Evaluation the Merdeka Belajar Kampus Merdeka Programme in Indonesia:: Sustainability and Challenges - Milwan, Milwan; Suharno, Suharno; Prasetyo, Danang (International Journal of Multidisciplinary Sciences, 2024)
This study aims to evaluate the MBKM (Merdeka Belajar Kampus Merdeka) Programme in Indonesia, describe sustainability, and challenges in implementing the programme. This research uses descriptive qualitative research by utilising data sources from books, articles, and related journals. The data collection technique was carried out by reviewing and analysing documents from several universities that have implemented the programme. The result of this study is that the universities that became the sample in the evaluation of MBKM implementation did not all implement the programme. Although there are universities that implement the programme, the percentage is still low. Therefore, universities need to do several things to improve it: 1) socialisation and inspire/motivate students to get involved in the programme. One of the strategies that can be anticipated to overcome the difficulties in producing outcomes that are aware of scientific and technological advances and able to compete in global progress is to design programme policies; 2) involve cooperation with several partners outside the college to equip students with MBKM programme experiences that are in accordance with student preferences; 3) colleges need to pay attention to the interests of students in implementing MBKM programmes, especially internship programmes that require extra funds. In addition, to support this programme, it is necessary to innovate learning models, collaborate with partners outside the campus, and adjust the study programme curriculum to be more adaptive in preparing graduates for the world of work.